Nature-based coastal flood protection: Lessons from the Caribbean and the Philippines - da Cruz e Sousa, Ricardo; Jamero, Laurice; Behar, David; Frederick, Nealla; Naipal, Sieuwnath; Pelindingue, Ma. Villa; Sulima, Norman (Journal of Coastal and Riverine Flood Risk, 2025)
This short communication examines four case studies from the Caribbean and the Philippines to summarize practical lessons on the implementation of nature-based solutions (NbS) for coastal flood protection. Each project, ranging from hybrid breakwaters to mangrove restoration, illustrates the benefits of integrating ecological restoration with participatory governance to enhance coastal resilience. Findings highlight that the effectiveness of NbS is highly site-specific, contingent upon local ecological conditions, governance structures, and socio-economic factors. While these interventions can offer significant co-benefits, including erosion control, biodiversity enrichment, and alternative livelihoods, challenges persist related to maintenance, funding, institutional coordination, and risk of maladaptation. This communication underscores the need to embed NbS within broader adaptation frameworks, combining scientific knowledge and community engagement to achieve durable outcomes. These insights are particularly relevant for low-lying coastal regions and small island developing states facing rising sea levels and intensifying storm impacts.